The identification of targeting peptides and tumour associated antigens for the treatment and early detection of triple negative breast cancer - Wilde, Megan (2023)
Breast cancer (BCa) is the most common type of non-cutaneous cancer globally. Despite advances in screening methods and treatment regimens, the malignancy leads to the most female cancer-related deaths each year. An aggressive subtype of breast cancer which often presents at a high histological grade is triple negative breast cancer (TNBC). TNBC is characterised by the absence of estrogen and progesterone receptor expression, as well as a lack of HER2 over-expression. TNBC currently has the worse prognosis among the molecular subtypes. However, early diagnosis and the development of targeted treatment may improve patient outcome.